Selective Secretion of KDEL-Bearing Proteins: Mechanisms and Functions - Palazzo, F. C.; Sitia, R.; Tempio, T. (Frontiers in Cell and Developmental Biology, 2022)
In multicellular organisms, cells must continuously exchange messages with the right meaning, intensity, and duration. Most of these messages are delivered through cognate interactions between membrane and secretory proteins. Their conformational maturation is assisted by a vast array of chaperones and enzymes, ensuring the fidelity of intercellular communication. These folding assistants reside in the early secretory compartment (ESC), a functional unit that encompasses endoplasmic reticulum, intermediate compartment and cis-Golgi. Most soluble ESC residents have C-terminal KDEL-like motifs that prevent their transport beyond the Golgi. However, some accumulate in the ER, while others in downstream stations, implying different recycling rates. Moreover, it is now clear that cells can actively secrete certain ESC residents but not others. This essay discusses the physiology of their differential intracellular distribution, and the mechanisms that may ensure selectivity of release.